JUDGE’S ATTITUDE TOWARDS THE MEDIATOR’S RECOMMENDATION REGARDING THE BAD FAITH PARTY AND MEDIATION FEES ISSUE - Baried, Rizky Ramadhan; Jamil, Abdul (Faculty of Law Universitas Padjadjaran, 2023)
This article was the result of research in 2021 with normative research. The formulations of the problems are: 1) What is the consideration of the panel of judges on the recommendation of the mediator regarding the sanctions for payment of mediation fees for parties who are declared to have no good intentions; 2) What is the procedure for payment of mediation fees by these parties. The conclusions are: 1) There is no data on the mediator's recommendation regarding paying mediation fees. It is not immediately followed up if the panel of judges receives it. The judges continue to examine the recommendation of providing justice so that the defendant does not feel more burdened so that the recommendation is not included in the court’s product; and 2) The procedure for payment of mediation fees is carried out together with the accumulated principal costs of the case by complying with the principles of execution. This study advises the Supreme Court of the Republic of Indonesia that there should be a mechanism agreed upon by both parties to jointly consign the amount of money that is expected to be used in the mediation process